Congenital muscular dystrophies in China. Issue 3 (6th June 2019) - Ge, Lin; Zhang, Cheng; Wang, Zhaoxia; Chan, Sophelia H.S.; Zhu, Wenhua; Han, Chunxi; Zhang, Xiaoli; Zheng, Hong; Wu, Liwen; Jin, Bo; Shan, Jingli; Mao, Bing; et al.
Abstract: Congenital muscular dystrophies (CMDs) are clinically and genetically heterogeneous conditions. We launched a nationwide study to determine the frequency of CMD in the Chinese population and assess the status of diagnosis and disease management for CMD in China. Cases were chosen from databases in 34 tertiary academic hospitals from 29 first‐level administrative divisions (provinces, municipalities, autonomous regions, and special administrative regions), and medical records were reviewed to confirm the diagnoses. The study included 409 patients, of those patients who consented to genetic testing (n = 340), mutations were identified in 286 of them. The most common forms identified were LAMA2 ‐related CMD (36.4%), followed by COL6‐related CMD (23.2%) and α‐dystroglycanopathy (21.0%). The forms of CMD related to mutations in LMNA and SEPN1 were less frequent (12.5% and 2.4%, respectively). We also recorded a significant difference in the diagnostic capabilities and disease management of CMD, with this being relatively backward in research centers from less developed regions. We provide, for the first time, comprehensive epidemiologic information of CMD in a large cohort of Chinese people. To our knowledge, this is the largest sample size of its kind so far highlighting the prevalence of CMD in China. Abstract :